Pengaruh Sikap Individu, Pendidikan, dan Pengalaman Kerja Serta Kaitannya Terhadap Etos Kerja Perusahaan CV Buana Sejara Jaya Abadi Bekasi - Akhmad Zaqi Amani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this research is to describe (1) the influence of individual attitudes on employee performance, (2) the influence of education level on employee performance, (3) the influence of work experience on employee performance, and (4) the influence of work ethic on employee performance at CV Buana Sejara Jaya Abadi Bekasi. This research is classified as quantitative research. The population is employees of CV Buana Sejara Jaya Abadi Bekasi. The sample for this research was 50 respondents. The data collection method uses a questionnaire method, while the data analysis technique uses multiple regression analysis and classical assumption tests consisting of normality tests, multicollinearity tests, and heteroscedasticity tests. The results of the analysis show that (1) Individual attitudes have a positive effect on employee performance. This means that the better the individual worker's attitude, the better the employee's performance. (2) Education has a positive effect on employee performance. This means that the better the level of education obtained, the better the employee's performance. (3) Work experience has a positive effect on employee performance. This means that the more employees have worked before, the better the employee's performance. (4) Work ethic simultaneously influences employee performance. This means that the better the individual attitude, education level and work experience of employees, the better the performance of CV Buana Sejara Jaya Abadi employees.